Application of structural dynamics in earthquake and wind engineering. - Pacheco, Benito M. (Philippine Engineering Journal)
Using minimal mathematics, extensive reference to the technical literature, and selected figures and tables, state of the art concepts of structural dynamics are introduced as applied to seismic and wind induced vibrations. Physical interpretations of mathematical concepts, and practical concerns of civil structural engineer are emphasized. The presentation attempts to highlight some similarities and also sharpen certain contrasts between earthquake and wind effects.